55.7k views
0 votes
Solve this equation for n.

-5(4n - 2.4) + 2(1.3 + 6n) = -5.4​

User Minichate
by
4.7k points

2 Answers

4 votes

Answer:

n = 2.5

Explanation:

distribute

-20n + 12 + 2.6 + 12n = -5.4

combine terms

-8n + 14.6 = -5.4

subtract 14.6 from both sides

-8n = -20

divide by -8

n = 2.5

User Alejdg
by
4.6k points
6 votes

Hi there!

n = 2.5

-5(4n - 2.4) + 2(1.3 + 6n) = -5.4

Distribute the coefficients outside of the parenthesis:

-5(4n) - 5(-2.4) + 2(1.3) + 2(6n) = -5.4

-20n + 12 + 2.6 + 12n = -5.4

Combine like terms:

-8n + 14.6 = -5.4

Subtract 14.6 from both sides:

-8n = -20

Divide both sides by -8:

-8n/(-8) = -20/(-8)

n = 2.5

User Jaques
by
4.6k points